A fuzzy inference system approach for habitat suitability index modeling: A case study of Bachman’s sparrow - Cassio Auguto Ussi Monti; Casey Eugene Phillips; Joseph Peter Roise; John Paul McTague; Christopher Moorman; Rachel Cook (Ecological Modelling, 2026)

Marine heatwaves disrupt the culling of Crown-of-Thorns Starfish on the Great Barrier Reef - Kailash Cook; Christina Skinner; Yves-Marie Bozec; Peter J Mumby (Coral Reefs, 2026)
Crown-of-Thorns Starfish (CoTS) predation poses an enduring threat to coral health on the Great Barrier Reef (GBR), driving substantial investment in research and control efforts. However, how CoTS respond to heat stress in situ remains uncertain, limiting our ability to optimise control efforts. We analysed 33 years of CoTS control records, including pre-culling surveys (manta tows) and cull data, with satellite-derived thermal stress metrics to investigate how heat stress influences CoTS detections and culling effectiveness patterns across the GBR. CoTS detections on pre-culling surveys declined significantly with cumulative heat stress, decreasing by 22% per °C-week increase in Degree Heating Weeks (DHW) to a maximum absolute decrease of 95% at 12°C-weeks. Cull data showed 9–14% fewer CoTS culled per dive per °C-week depending on size. These patterns underpin a seasonal response: CoTS culling efficiency peaks in winter and declines in summer, with deeper and longer summer troughs under higher annual heat stress. Culling is triggered when pre-culling surveys meet thresholds for CoTS feeding scars or abundance. We find the false-positive rate, cases where no CoTS are later encountered, is higher (50%) when culls are triggered by scars than by sightings (36%), indicating scars are a less reliable indicator of CoTS presence. Finally, while coral and CoTS populations often exhibit a dynamic balance on controlled reefs, this equilibrium deteriorates when heat stress exceeds ~6 °C-weeks, leading to accelerated coral loss compounded by CoTS presence. This highlights the need for adaptive management strategies that incorporate seasonal and thermal shifts in CoTS behaviour, especially as ocean warming intensifies.

The use of pumping for hydraulic characterisation of dykes - Vair J. Pointon; Ilka Wallis; Daniel Partington; Paul Hedley; Peter G. Cook (Hydrogeology Journal, 2026)
Faults and dykes can control groundwater flow, acting as barriers, conduits, or composite conduit–barrier systems. This study investigates dyke hydraulic behaviour using numerical modelling of field-scale pumping tests at two sites in Western Australia, supported by a uniquely detailed hydrogeological dataset. At each site, pumping tests were conducted across dykes that impeded groundwater flow, as evidenced by asymmetric drawdown cones and delayed responses in observation wells situated across the dyke from the pumping well. High-resolution three-dimensional geological frameworks were developed, and transient groundwater flow models were calibrated using automated inversion with and without spatially variable parameterisation (pilot points) to represent heterogeneity. In all calibrated models, the horizontal hydraulic conductivity ( K h ) of dykes was estimated to be one to eight orders of magnitude lower than that of the surrounding formations. Representation of dykes in the model produced the largest improvement in model fit at both sites, reducing the parameterisation objective function by one to two orders of magnitude relative to model parameterisations without dykes. Further improvements in model fit were achieved by introducing heterogeneity into formations, dykes or both. Although including formation heterogeneity reduced posterior uncertainty in dyke K h estimates, posterior variance patterns revealed that, in some locations, calibration preferentially adjusted K h in formations adjacent to dykes rather than within the dykes. Dyke K h was tightly constrained in areas with available field data and observable drawdown. These findings demonstrate the importance of representing structural features when interpreting pumping-test responses in structurally complex groundwater systems.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Microvertebrates from the Cliff End Bone Bed (Wealden, Lower Cretaceous), East Sussex, UK - Johnny Clavo Yamahuchi; Elizabeth Cook; Christopher J. Duffin; Peter A. Austen; Steven C. Sweetman; Pamela G. Gill; Claudia Hildebrandt; Tim Tomkinson; Michael J. Benton (Proceedings of the Geologists' Association, 2026)

Australian stingless bees exhibit greater sensitivity to dimethoate than Apis mellifera: implications for pesticide risk assessment - Gaurav Singh; James C. Makinson; Mary Finlay Doney; Onyeka Peter Nzie; James M. Cook; Robert N. Spooner-Hart (Pesticide Biochemistry and Physiology, 2026)

Cognition as a Conservation Tool: A Case Study of Florida Manatees and Boat Strikes - Gordon B. Bauer; Charles J. Deutsch; Roger L. Reep; Wendi Fellner; Tabitha Gunnars; Peter F. Cook; Heidi E. Harley; Athena M. Rycyk (Marine Mammal Science, 2026)
Boat strikes injure and kill large numbers of Florida manatees ( Trichechus manatus latirostris ) each year. Management actions taken to mitigate this threat can be potentially enhanced by consideration of manatee cognitive processes. The role of cognition in marine mammal conservation has received little consideration in the literature. Here, we integrate discoveries from laboratory research on auditory sensory processes and perception with findings from field studies of how manatees respond to motorized vessels and the effect of the ambient soundscape on response times to boat noise. We incorporate that information into recommendations for manatee management to further reduce the risk of collisions. We also suggest lines of research to investigate other relevant cognitive issues—including attention, learning, memory, and decision‐making—to improve conservation efforts and understanding of manatee behavior.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Lessons learned from screening potential other effective area‐based conservation measures - Carly N. Cook; Madhu Rao; Peter J. Clyne; Vanessa Rathbone; Christian Barrientos; Antonio Boveda; Alex Diment; Jorge Parra; Valeria Falabella; Matthew Linke; Deo Kujirakwinja; Stephane Ostrowski; et al. (Conservation Biology, 2026)
Other effective area‐based conservation measures (OECMs) are sites that deliver effective biodiversity outcomes irrespective of their management objectives. These areas are widely expected to play an important role in efforts to protect 30% of Earth by 2030. Despite general guidance to support screening sites against the formal criteria to be OECMs, progress recognizing sites has been limited. To advance the ability to identify OECMs, we developed a questionnaire that translates the components of the broad formal guidance into statements that experts can use to screen potential OECMs. Twenty‐eight local experts used the questionnaire to evaluate a large global sample of 81 sites. Most sites evaluated were largely in good condition and had the potential to achieve conservation outcomes, but none met the criteria to be considered OECMs. The most common challenges are related to threat management, adequate resourcing, and the ability to demonstrate that governance and management are achieving effective and sustained conservation outcomes. Based on the formal International Union for Conservation of Nature guidance, sites that only partially meet the relevant criteria remain candidate OECMs. Our questionnaire provides a nuanced way to assess OECMs that can help identify what support sites need to meet the necessary criteria. With effective long‐term conservation outcomes unable to be demonstrated for so many important conservation areas, our findings raise important questions about how to ensure area‐based conservation promotes positive and sustained outcomes for biodiversity.

From little things big things flow: the drivers of flood risk adaptation - Peter Kamstra; Nicholas Harrigan; Brian R. Cook (Journal of Hydrology, 2026)

Sea lions as a natural model for charting the developmental course following in utero exposure to domoic acid - Peter F. Cook; Colleen Reichmuth; Megan E. Moriarty; Alissa C. Deming; Vanessa Fravel Hoard; Cara Field; Frances Gulland (Harmful Algae, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Quantifying Fine Sediment Erosion From Unsealed Roads Draining to the Great Barrier Reef Before and After Applying Best Management Practices - Jeffrey Shellberg; David Klye; Jessie Price-Decle; Pedro Russell-Smith; Keith Cook; Tony Peter; Indigo Gambold; James Dobson (Environmental Management, 2026)

Exploring Marine Mammal Cognition as a Conservation Tool - Gordon B. Bauer; Peter F. Cook; Heidi E. Harley; Jason Bruck; Mel Cosentino; Charles J. Deutsch; Nicola Erdsack; Wendi Fellner; Tabitha Gunnars; Heather Manitzas Hill; Sonia V. Kumar; Malin K. Lilley; et al. (Marine Mammal Science, 2026)
Cognition is an animal's real‐time adaptation system for responding to change. Rapid environmental change, often anthropogenic, is expanding the range and severity of challenges confronting wild animals. Effective conservation requires a multifaceted approach that includes animals' capacities. Large‐brained, long‐lived animals such as marine mammals often have extensive capability to adaptively modify their behavior due to their cognition, which comprises the mechanisms of information acquisition, processing, and flexible action. Consequently, current behavior need not be a final predictor of future behavior for these animals. This flexibility provides an underutilized and under examined point of leverage for humans interested in improving life outcomes for wild animals. In this team‐written, interdisciplinary paper, we argue that application of cognitive approaches may facilitate many conservation efforts directed toward marine mammals. Starting with a workshop on this topic at the 24th Biennial Conference on the Biology of Marine Mammals, scientists representing a wide range of disciplinary expertise addressed eight different conservation concerns for six marine mammal species and provided potential cognitive explanations of and interventions aimed at related behavior. Our treatment highlights the value of integrated laboratory and field research, and the importance of tight lines of communication between scientists and conservation managers.

Investigating the physicochemical parameters that drive geosmin production in benthic cyanobacterial systems - Florence Choo; David Cook; Peter Hobson (Water Research, 2025)

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

Influence of aquifer properties on optimal location and duration of groundwater level monitoring to predict aquifer recovery after mine closure - Luis Camilo Suescun; Peter Cook; Daniel Partington; Rui Hugman; Ilka Wallis (Journal of Hydrology, 2025)

Corrigendum to “Influence of aquifer properties on optimal location and duration of groundwater level monitoring to predict aquifer recovery after mine closure” [J. Hydrol. 631 (2025) 133686] - Luis Camilo Suescun; Peter Cook; Daniel Partington; Rui Hugman; Ilka Wallis (Journal of Hydrology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Marker trait association analysis identified a novel quantitative trait loci (QTL) for Fusarium wilt resistance in chickpea (Cicer arietinum L.) - Dagnachew Bekele; Kassahun Tesfaye; Asnake Fikre; Noelia C. Garcia; Peter L. Chang; Douglas R. Cook (Euphytica, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Hydrochemical evolution of groundwater in a semi-arid environment verified through natural tracer and geochemical modelling, northwest Australia - Shawan Dogramaci; Ilka Wallis; Peter Cook; Allan Kneeshaw (Applied Geochemistry, 2025)

Worldwide abalone production: an update - Peter A. Cook (New Zealand Journal of Marine and Freshwater Research, 2025)
This paper presents a review of information presented at the 11th International Abalone Symposium, held in New Zealand in February 2023, where representatives from a range of countries presented data on abalone production in their region. The total quantity of abalone produced on farms worldwide has increased significantly in recent years, whilst abalone fisheries have declined. Production from fisheries was almost 20,000 mt in the 1970s but was only about 5850 mt in 2020/21. Over the same period, farm production has increased from negligible quantities in the 1970s to 243,506 mt in 2020/21. China and South Korea produce the largest quantities of abalone. Illegal exploitation, particularly in South Africa, Australia and New Zealand, is still a significant problem. Prices paid for abalone on the world market are variable, and depend on a number of factors. China is both a major producer and consumer of abalone, and although there was a fear that over‐production in China could be a threat to worldwide market prices, this has not been the experience to date.

Identifying resilient areas for seagrass restoration by integrating suitability modelling and climate forecasting - Oliver Dalby; Mary A. Young; Emma L. Jackson; Yi Mei Tan; Rhys A. Coleman; Kathy Cinque; Peter Yeates; Perran Cook; Peter I. Macreadie; Daniel Ierodiaconou; Craig D.H. Sherman (Estuarine, Coastal and Shelf Science, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Mid-to Late Holocene East Antarctic ice-core tephrochronology: Implications for reconstructing volcanic eruptions and assessing their climatic impacts over the last 5,500 years - Peter M. Abbott; Joseph R. McConnell; Nathan J. Chellman; Sepp Kipfstuhl; Maria Hörhold; Johannes Freitag; Eliza Cook; William Hutchison; Michael Sigl (Quaternary Science Reviews, 2024)

Factors Influencing Health-Related Quality of Life of Patients with Spinocerebellar Ataxia - Niklas Weber; Maresa Buchholz; Anika Rädke; Jennifer Faber; Tanja Schmitz-Hübsch; Heike Jacobi; Thomas Klockgether; Wolfgang Hoffmann; Bernhard Michalowsky; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; et al. (The Cerebellum, 2024)
Background Little is known about the progression of health-related quality of life (HRQoL) and predicting factors in spinocerebellar ataxia (SCA). Such knowledge is crucial to identify modifiable factors promoting everyday life with SCA and attenuating HRQoL decline. Objectives This study is to assess HRQoL progression and identify factors affecting SCA patients’ HRQoL. Methods Longitudinal data (three-year follow-up) of 310 SCA patients of the European SCA3/Machado-Joseph-Disease Initiative (ESMI) (2016-2022) and 525 SCA patients (SCA1, SCA2, SCA3 or SCA6) of the EUROSCA natural history study cohort (2006–2015) were assessed. Both large cohort studies share standardized assessments of clinical measures, SARA, INAS, PHQ-9, and HRQoL (EQ-5D-3L). The association between HRQoL and clinical measures was assessed by Spearman Correlation (r s ). Multivariable panel regression models were performed to evaluate the impact of patients’ socio-demographics, age of onset, SCA type and body mass index (BMI), and clinical measures on HRQoL progression. Results HRQoL significantly decreased over one (− 0.014, p = 0.095), two (− 0.028, p = 0.003), and three years (− 0.032, p = 0.002). Ataxia severity and mental health strongly correlated with HRQoL (r s SARA = − 0.589; r s PHQ-9 = − 0.507). HRQoL more intensively declined in male (ß = − 0.024, p = 0.038) patients with an earlier age of onset (ß = 0.002, p = 0.058). Higher progression of ataxia severity (ß = − 0.010, p ≤ 0.001), mental health problems (ß = − 0.012, p < 0.001), and higher BMI (ß = − 0.003, p = 0.029) caused more severe decline of patients’ HRQoL over time. Discussion In absence of curative treatments, stronger focus on mental health and weight influence could help clinical evaluation and accompany treatment improving SCA patients’ HRQoL, especially in male patients with early disease onset.

Need and vision for global medium-resolution Landsat and Sentinel-2 data products - Volker C. Radeloff; David P. Roy; Michael A. Wulder; Martha Anderson; Bruce Cook; Christopher J. Crawford; Mark Friedl; Feng Gao; Noel Gorelick; Matthew Hansen; Sean Healey; Patrick Hostert; et al. (Remote Sensing of Environment, 2024)

Examining the effects of soil entrainment during nuclear cloud rise on fallout predictions using a multiscale atmospheric modeling framework - Katherine A. Lundquist; Robert S. Arthur; Stephanie Neuscamman; Joseph P. Morris; Christian R. Scullard; Andrew W. Cook; Nathan G. Wimer; Peter Goldstein; Gregory D. Spriggs; Lee G. Glascoe; John S. Nasstrom (Journal of Environmental Radioactivity, 2023)

Simulating carbon accumulation and loss in the central Congo peatlands - Dylan M. Young; Andy J. Baird; Paul J. Morris; Greta C. Dargie; Y. Emmanuel Mampouya Wenina; Mackline Mbemba; Arnoud Boom; Peter Cook; Richard Betts; Eleanor Burke; Yannick E. Bocko; Sarah Chadburn; et al. (Global Change Biology, 2023)
Peatlands of the central Congo Basin have accumulated carbon over millennia. They currently store some 29 billion tonnes of carbon in peat. However, our understanding of the controls on peat carbon accumulation and loss and the vulnerability of this stored carbon to climate change is in its infancy. Here we present a new model of tropical peatland development, DigiBog_Congo, that we use to simulate peat carbon accumulation and loss in a rain‐fed interfluvial peatland that began forming ~20,000 calendar years Before Present (cal. yr BP, where ‘present’ is 1950 CE). Overall, the simulated age‐depth curve is in good agreement with palaeoenvironmental reconstructions derived from a peat core at the same location as our model simulation. We find two key controls on long‐term peat accumulation: water at the peat surface (surface wetness) and the very slow anoxic decay of recalcitrant material. Our main simulation shows that between the Late Glacial and early Holocene there were several multidecadal periods where net peat and carbon gain alternated with net loss. Later, a climatic dry phase beginning ~5200 cal. yr BP caused the peatland to become a long‐term carbon source from ~3975 to 900 cal. yr BP. Peat as old as ~7000 cal. yr BP was decomposed before the peatland's surface became wetter again, suggesting that changes in rainfall alone were sufficient to cause a catastrophic loss of peat carbon lasting thousands of years. During this time, 6.4 m of the column of peat was lost, resulting in 57% of the simulated carbon stock being released. Our study provides an approach to understanding the future impact of climate change and potential land‐use change on this vulnerable store of carbon.

PyPlume: A toolkit for rapid ocean surface transport assessments - Jerry Yan; Thomas Cook; Allison Ho; Mark Otero; Peter A. Rogowski; Mika Siegelman; Eric Terrill; Sophia Merrifield (Environmental Modelling & Software, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Health-Related Quality of Life in Patients with Spinocerebellar Ataxia: a Validation Study of the EQ-5D-3L - Maresa Buchholz; Niklas Weber; Anika Rädke; Jennifer Faber; Tanja Schmitz-Hübsch; Heike Jacobi; Feng Xie; Thomas Klockgether; Bernhard Michalowsky; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; et al. (The Cerebellum, 2023)
Although health-related quality of life (HRQoL) has developed into a crucial outcome parameter in clinical research, evidence of the EQ-5D-3L validation performance is lacking in patients with spinocerebellar ataxia (SCA) types 1, 2, 3, and 6. The objective of this study is to assess the acceptability, validity, reliability, and responsiveness of the EQ-5D-3L. For n = 842 predominantly European SCA patients of two longitudinal cohort studies, the EQ-5D-3L, PHQ-9 (Patient Health Questionnaire), and ataxia-specific clinical assessments (SARA: Scale for Assessment and Rating of Ataxia; ADL: activities of daily living as part of Friedreich’s Ataxia Rating Scale; INAS: Inventory of Non-Ataxia Signs) were assessed at baseline and multiple annual follow-ups. The EQ-5D-3L was evaluated regarding acceptability, distribution properties, convergent and known-groups validity, test-retest reliability, and effect size measures to analyze health changes. The non-item response was low (EQ-5D-3L index: 0.8%; EQ-VAS: 3.4%). Ceiling effects occurred in 9.9% (EQ-5D-3L) and 3.0% (EQ-VAS) with a mean EQ-5D-3L index of 0.65 ± 0.21. In total, convergent validity showed moderate to strong Spearman’s rho ( r s > 0.3) coefficients comparing EQ-5D-3L and EQ-VAS with PHQ-9, SARA, ADL, and INAS. EQ-5D-3L could discriminate between groups of age, SARA, ADL, and INAS. Intra-class correlation coefficients (EQ-5D-3L ICC : 0.95/EQ-VAS ICC : 0.88) and Kappa statistics (range 0.44 to 0.93 for EQ-5D-3L items) indicated tolerable reliability. EQ-5D-3L shows small (effect size < 0.3) to moderate (effect size 0.3–0.59) health changes regarding ataxia severity. The analysis confirms an acceptable, reliable, valid, and responsive recommended EQ-5D-3L in SCA patients, measuring the HRQoL adequately, besides well-established clinical instruments.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Adaptation constraints and prospects for future research priorities in lowland rice-based farming systems: learning experiences from Northwest Cambodia - Van Touch; Rebecca Cross; Clemens Grünbühel; Floris Van Ogtrop; Peter Ampt; Try Yorn; Robert John Martin; Brian R. Cook; Daniel K. Y. Tan (Environment, Development and Sustainability, 2023)
Sustainable agricultural development not only addresses global food insecurity but may also alleviate poverty by enriching the lives of millions of smallholder farmers. Improving the sustainability and profitability of agriculture where smallholders are dominant creates profound impacts because small landholding farmers produce approximately 70–80% of the global food. The need for a thorough understanding of the factors affecting farmers’ adoption of agricultural technologies and practices has been identified from extant literature as an important research gap. Responding to the research gap and need, this study examined the challenges that prevent farm households from adopting improved farming practices and/or technologies in Banteay Meanchey and Battambang provinces in Northwest Cambodia. A total of 524 rice producing farm household representatives were randomly selected from a household database maintained by the local government authorities. A mixed methods approach was used in the study including semi-structured interviews followed by in-depth interviews, field observations, and literature review. Farmers were found to be confronted with a range of challenges and concerns, including soil degradation, weeds, diseases, insect pests, high production costs, flooding, droughts, changing rainfall pattern, and unreliable rainfall distribution. The research findings demonstrate that improved crop production practices (e.g., adopting mechanised direct seeding methods of crop establishment, maintaining and improving soil health through crop residue retention, growing cover crops, etc.) and better resource use efficiency (e.g., reducing seeding rates to less than 100 kg/ha, being more strategic in the use of integrated nutrient, weed, and pest management strategies, etc.) can be a starting point for sustainable intensification of rice production. This transition towards intensifying paddy production sustainably may become even more effective through a clear understanding of local contexts, farm household characteristics, available resources, and the farm management practices and constraints. We observed that farmers and their associations have yet to be fully recognised as partners and actors in Cambodia. Instead, they tend to be viewed as beneficiaries and recipients of improved practices and technologies. We, therefore, propose that farmers and their associations be acknowledged and included in a process of co-creation of knowledge-practices. Such partnerships will enable the inclusion of factors (e.g., production costs, production risks, complexity and practicability of implementations, product market and prices, etc.) shown to influence farmers’ adoption of innovative farming practices and technologies. The original contribution of this article is a real-world account of the constraints and limitations experienced by smallholder rice farmers in Cambodia, which are connected to future research and development priorities in the region.

Neurodevelopmental outcomes in children and adults with Fetal Valproate Spectrum Disorder: A contribution from the ConcePTION project - Matthew Bluett-Duncan; Denise Astill; Rana Charbak; Jill Clayton-Smith; Susan Cole; Penny A. Cook; Jo Cozens; Karen Keely; Jacki Morris; Raja Mukherjee; Emma Murphy; Peter Turnpenny; et al. (Neurotoxicology and Teratology, 2023)

Adult-onset epilepsy and hippocampal pathology in a California sea lion (Zalophus californianus): A case study of suspected in utero exposure to domoic acid - David D.R. Krucik; Peter Cook; Michael Cathey; Jennifer M. Meegan; Forrest M. Gomez; William Van Bonn; Carolina Le-Bert (NeuroToxicology, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

ACPSEM position paper: the safety of magnetic resonance imaging linear accelerators - Nick Cook; Nikki Shelton; Stephen Gibson; Peter Barnes; Reza Alinaghi-Zadeh; Michael G. Jameson (Physical and Engineering Sciences in Medicine, 2023)
Magnetic Resonance Imaging linear-accelerator (MRI-linac) equipment has recently been introduced to multiple centres in Australia and New Zealand. MRI equipment creates hazards for staff, patients and others in the MR environment; these hazards must be well understood, and risks managed by a system of environmental controls, written procedures and a trained workforce. While MRI-linac hazards are similar to the diagnostic paradigm, the equipment, workforce and environment are sufficiently different that additional safety guidance is warranted. In 2019 the Australasian College of Physical Scientists and Engineers in Medicine (ACPSEM) formed the Magnetic Resonance Imaging Linear-Accelerator Working Group (MRILWG) to support the safe clinical introduction and optimal use of MR-guided radiation therapy treatment units. This Position Paper is intended to provide safety guidance and education for Medical Physicists and others planning for and working with MRI-linac technology. This document summarises MRI-linac hazards and describes particular effects which arise from the combination of strong magnetic fields with an external radiation treatment beam. This document also provides guidance on safety governance and training, and recommends a system of hazard management tailored to the MRI-linac environment, ancillary equipment, and workforce.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Groundwater-level recovery following closure of open-pit mines - Caglar Bozan; Ilka Wallis; Peter G. Cook; Shawan Dogramaci (Hydrogeology Journal, 2022)
Open-pit mining has increased substantially over the past two decades. Many currently operating open-pit mines are facing the end of mine-life over the next few decades and, increasingly, focus is shifting towards mine-closure planning that provides evidence on available closure options under the given geological, hydro(geo)logical and climatic conditions. This study uses synthetic groundwater modelling to build basic process understanding of closure options and how these will determine the formation of pit lakes. This governs the long-term pit lake water quality and how postmining landscapes may be utilised. Simulations show that the recovery time of postmining groundwater levels increases with decreasing aquifer transmissivity. Final postmining water tables are predominantly controlled by the implemented mine closure options and climatic conditions. The most important decision is, thereby, whether to backfill the pit to above the water table or allow a pit lake to develop. Under moderately transmissive aquifer settings, backfilling of pits leads to rapidly rising groundwater levels within the first decade after mining, with water-table recoveries of above 70%. If mine voids remain unfilled, evaporation from the pit lake surface becomes a governing factor in determining whether the unfilled mine pit becomes a terminal sink for groundwater. Lake levels may remain subdued by several 10s of metres in arid to semiarid climates. If surplus surface water can be diverted into open pits, rapid filling can accelerate groundwater recovery of open pits in regions of low permeability. This is a less successful management option in transmissive aquifers.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Rapid radiation of Southern Ocean shags in response to receding sea ice - Nicolas J. Rawlence; Alexander T. Salis; Hamish G. Spencer; Jonathan M. Waters; Lachie Scarsbrook; Kieren J. Mitchell; Richard A. Phillips; Luciano Calderón; Timothée R. Cook; Charles‐André Bost; Ludovic Dutoit; Tania M. King; et al. (Journal of Biogeography, 2022)
Aim Understanding how natural populations respond to climatic shifts is a fundamental goal of biological research in a fast‐changing world. The Southern Ocean represents a fascinating system for assessing large‐scale climate‐driven biological change, as it contains extremely isolated island groups within a predominantly westerly, circumpolar wind and current system. Blue‐eyed shags represent a paradoxical seabird radiation—a circumpolar distribution implies strong dispersal capacity yet their species‐rich nature suggests local adaptation and isolation. Here we attempt to resolve this paradox in light of the history of repeated cycles of climate change in the Southern Ocean. Location Southern Ocean. Taxa 16 species and subspecies of blue‐eyed shags (Phalacrocoracidae; Leucocarbo spp.). Methods We use mitochondrial and nuclear sequence data from individuals across the geographical range of the genus to conduct the first comprehensive, time‐calibrated phylogenetic analyses and ancestral‐range biogeographical reconstructions of the blue‐eyed shags. Results The origins of many island‐endemic lineages are remarkably recent, consistent with a recent high‐latitude circumpolar radiation in the Pliocene or Early Pleistocene. This recent sub‐Antarctic expansion contrasts with significantly deeper lineages detected in South America and, to a lesser extent, New Zealand. These regions, particularly South America, acted as glacial refugia and sources for multiple waves of post‐glacial dispersal. Main conclusions The blue‐eyed shag paradox is resolved, with at least two waves of dispersal, linked to interglacial cycles, explaining the current distribution and diversity. Descendants of a Pliocene or Early Pleistocene wave of dispersal out of South America survive in the New Zealand region. In contrast, taxa distributed on sub‐Antarctic islands originated much later, possibly since the Last Glacial Maximum. Blue‐eyed shags therefore represent a powerful model system—comprising several natural replicates—for studying the early stages of founder‐event speciation and adaptation in a Southern‐Ocean bird group.

Cooperative breeding and the emergence of multilevel societies in birds - Ettore Camerlenghi; Alexandra McQueen; Kaspar Delhey; Carly N. Cook; Sjouke A. Kingma; Damien R. Farine; Anne Peters (Ecology Letters, 2022)
Multilevel societies (MLSs), where social levels are hierarchically nested within each other, are considered one of the most complex forms of animal societies. Although thought to mainly occurs in mammals, it is suggested that MLSs could be under‐detected in birds. Here, we propose that the emergence of MLSs could be common in cooperatively breeding birds, as both systems are favoured by similar ecological and social drivers. We first investigate this proposition by systematically comparing evidence for multilevel social structure in cooperative and non‐cooperative birds in Australia and New Zealand, a global hotspot for cooperative breeding. We then analyse non‐breeding social networks of cooperatively breeding superb fairy‐wrens ( Malurus cyaneus ) to reveal their structured multilevel society, with three hierarchical social levels that are stable across years. Our results confirm recent predictions that MLSs are likely to be widespread in birds and suggest that these societies could be particularly common in cooperatively breeding birds.

Viral-Like Particles Are Associated With Endosymbiont Pathology in Florida Corals Affected by Stony Coral Tissue Loss Disease - Thierry M. Work; Tina M. Weatherby; Jan H. Landsberg; Yasunari Kiryu; Samantha M. Cook; Esther C. Peters (Frontiers in Marine Science, 2021)
Stony coral tissue loss disease (SCTLD) was first documented in 2014 near the Port of Miami, Florida, and has since spread north and south along Florida’s Coral Reef, killing large numbers of more than 20 species of coral and leading to the functional extinction of at least one species, Dendrogyra cylindrus . SCTLD is assumed to be caused by bacteria based on presence of different molecular assemblages of bacteria in lesioned compared to apparently healthy tissues, its apparent spread among colonies, and cessation of spread of lesions in individual colonies treated with antibiotics. However, light microscopic examination of tissues of corals affected with SCTLD has not shown bacteria associated with tissue death. Rather, microscopy shows dead and dying coral cells and symbiotic dinoflagellates (endosymbionts) indicating a breakdown of host cell and endosymbiont symbiosis. It is unclear whether host cells die first leading to death of endosymbionts or vice versa. Based on microscopy, hypotheses as to possible causes of SCTLD include infectious agents not visible at the light microscopy level or toxicosis, perhaps originating from endosymbionts. To clarify this, we examined corals affected with SCTLD and apparently healthy corals using transmission electron microscopy. Endosymbionts in SCTLD-affected and apparently healthy corals consistently had varying degrees of pathology associated with elongated particles compatible in morphology with filamentous positive single-stranded RNA viruses of plants termed anisometric viral-like particles (AVLP). There was apparent progression from early to late replication of AVLP in the cytoplasm of endosymbionts adjacent to or at times within chloroplasts, with morphologic changes in chloroplasts consistent with those seen in plant cells infected by viruses. Coral host cell pathology appeared limited to massive proliferation and lysis of mucus cells. Based on these findings, we hypothesize that SCTLD is a viral disease of endosymbionts leading to coral host death. Efforts to confirm the presence of a virus associated with SCTLD through other means would be appropriate. These include showing the presence of a virus through molecular assays such as deep sequencing, attempts to grow this virus in the laboratory through culture of endosymbionts, localization of virus in tissue sections using immunohistochemistry or in situ hybridization, and experimental infection of known-virus-negative corals to replicate disease at the gross and microscopic level.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Conceptual uncertainties in groundwater and porewater fluxes estimated by radon and radium mass balances - Valentí Rodellas; Thomas C. Stieglitz; Joseph J. Tamborski; Pieter van Beek; Aladin Andrisoa; Peter G. Cook (Limnology and Oceanography, 2021)
Radium isotopes and radon are routinely used as tracers to quantify groundwater and porewater fluxes into coastal and freshwater systems. However, uncertainties associated with the determination of the tracer flux are often poorly addressed and often neglect all the potential errors associated with the conceptualization of the system (i.e., conceptual uncertainties). In this study, we assess the magnitude of some of the key uncertainties related to the determination of the radium and radon inputs supplied by groundwater and porewater fluxes into a waterbody (La Palme Lagoon, France). This uncertainty assessment is addressed through a single model ensemble approach, where a tracer mass balance is run multiple times with variable sets of assumptions and approaches for the key parameters determined through a sensitivity test. In particular, conceptual uncertainties linked to tracer concentration, diffusive fluxes, radon evasion to the atmosphere, and change of tracer inventory over time were considered. The magnitude of porewater fluxes is further constrained using a comparison of independent methods: (1) 224 Ra and (2) 222 Rn mass balances in overlying waters, (3) a model of 222 Rn deficit in sediments, and (4) a fluid‐salt numerical transport model. We demonstrate that conceptual uncertainties are commonly a major source of uncertainty on the estimation of groundwater or porewater fluxes and they need to be taken into account when using tracer mass balances. In the absence of a general framework for assessing these uncertainties, this study provides a practical approach to evaluate key uncertainties associated to radon and radium mass balances.

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Investigating food limitations in wild fisheries: the attendance and growth responses of fish at an anthropogenic feeding station within a temperate estuary - Denham G. Cook; Peter Jaksons; Alistair Jerrett (Journal of Fish Biology, 2020)
To investigate whether wild fish populations are food limited, this study explored whether the provision of supplementary food had a positive effect on the abundance, condition and growth characteristics of estuarine fish assemblages in New Zealand. Feed (7690 kg) was delivered from an anthropogenic feeding station over a 60‐week period to a naturally occurring assemblage of wild fish. Yellow‐eyed mullet ( Aldrichetta forsteri ) of juvenile, sub‐adult and newly matured size classes were the dominant species actively foraging at the feeding station throughout its operation, whereas larger piscivorous species visited and foraged from the feed station over the summer period only. Other species were present in the wider area of Nelson Haven, but not at the feed station. No obvious changes in the condition factor of yellow‐eyed mullet were observed across the period of monitoring, and no changes in their catchability were detected – although marked seasonal variation in catch rates was observed. Results from tag‐recapture data identify that the length‐based growth rates of yellow‐eyed mullet recaptured near the feed station were higher than those of tagged individuals recaptured at a nearby comparison site, and were higher than the growth rates observed in natural populations of yellow‐eyed mullet in the wider region. Shifts in the median size of fish, as observed by acoustic observations, agreed with the tag‐recapture data. Although some of the results identified were not amenable to statistical analyses, the attendance of yellow‐eyed mullet at the feeding station, in combination with the improved estimates of growth by most of the techniques employed, indicates that yellow‐eyed mullet are food limited in their natural environment and that the growth performance of these fish can be positively affected by the increased availability of food.

Large climate mitigation potential from adding trees to agricultural lands - Melissa Chapman; Wayne S. Walker; Susan C. Cook‐Patton; Peter W. Ellis; Mary Farina; Bronson W. Griscom; Alessandro Baccini (Global Change Biology, 2020)
While improved management of agricultural landscapes is promoted as a promising natural climate solution, available estimates of the mitigation potential are based on coarse assessments of both agricultural extent and aboveground carbon density. Here we combine 30 meter resolution global maps of aboveground woody carbon, tree cover, and cropland extent, as well as a 1 km resolution map of global pasture land, to estimate the current and potential carbon storage of trees in nonforested portions of agricultural lands. We find that global croplands currently store 3.07 Pg of carbon (C) in aboveground woody biomass (i.e., trees) and pasture lands account for an additional 3.86 Pg C across a combined 3.76 billion ha. We then estimate the climate mitigation potential of multiple scenarios of integration and avoided loss of trees in crop and pasture lands based on region‐specific biomass distributions. We evaluate our findings in the context of nationally determined contributions and find that the majority of potential carbon storage from integration and avoided loss of trees in crop and pasture lands is in countries that do not identify agroforestry as a climate mitigation technique.

Conjoint use of hydraulic head and groundwater age data to detect hydrogeologic barriers - Sarah K. Marshall; Peter G. Cook; Leonard F. Konikow; Craig T. Simmons; Shawan Dogramaci (Hydrogeology Journal, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

The global Microcystis interactome - Katherine V. Cook; Chuang Li; Haiyuan Cai; Lee R. Krumholz; K. David Hambright; Hans W. Paerl; Morgan M. Steffen; Alan E. Wilson; Michele A. Burford; Hans‐Peter Grossart; David P. Hamilton; Helong Jiang; et al. (Limnology and Oceanography, 2020)
Bacteria play key roles in the function and diversity of aquatic systems, but aside from study of specific bloom systems, little is known about the diversity or biogeography of bacteria associated with harmful cyanobacterial blooms (cyanoHABs). CyanoHAB species are known to shape bacterial community composition and to rely on functions provided by the associated bacteria, leading to the hypothesized cyanoHAB interactome, a coevolved community of synergistic and interacting bacteria species, each necessary for the success of the others. Here, we surveyed the microbiome associated with Microcystis aeruginosa during blooms in 12 lakes spanning four continents as an initial test of the hypothesized Microcystis interactome. We predicted that microbiome composition and functional potential would be similar across blooms globally. Our results, as revealed by 16S rRNA sequence similarity, indicate that M. aeruginosa is cosmopolitan in lakes across a 280° longitudinal and 90° latitudinal gradient. The microbiome communities were represented by a wide range of operational taxonomic units and relative abundances. Highly abundant taxa were more related and shared across most sites and did not vary with geographic distance, thus, like Microcystis , revealing no evidence for dispersal limitation. High phylogenetic relatedness, both within and across lakes, indicates that microbiome bacteria with similar functional potential were associated with all blooms. While Microcystis and the microbiome bacteria shared many genes, whole‐community metagenomic analysis revealed a suite of biochemical pathways that could be considered complementary. Our results demonstrate a high degree of similarity across global Microcystis blooms, thereby providing initial support for the hypothesized Microcystis interactome.

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

We need both natural and energy solutions to stabilize our climate - Bronson W. Griscom; Guy Lomax; Timm Kroeger; Joseph E. Fargione; Justin Adams; Lucy Almond; Deborah Bossio; Susan C. Cook‐Patton; Peter W. Ellis; Christina M. Kennedy; Joseph Kiesecker (Global Change Biology, 2019)

The Global High Frequency Radar Network - Hugh Roarty; Thomas Cook; Lisa Hazard; Doug George; Jack Harlan; Simone Cosoli; Lucy Wyatt; Enrique Alvarez Fanjul; Eric Terrill; Mark Otero; John Largier; Scott Glenn; et al. (Frontiers in Marine Science, 2019)

Protecting groundwater levels and ecosystems with simple management approaches - Saskia L. Noorduijn; Peter G. Cook; Craig T. Simmons; Stuart B. Richardson (Hydrogeology Journal, 2019)

Uncertainty assessment of spatial-scale groundwater recharge estimated from unsaturated flow modelling - Yueqing Xie; Russell Crosbie; Craig T. Simmons; Peter G. Cook; Lu Zhang (Hydrogeology Journal, 2019)

Treating risk as relational on shore platforms and implications for public safety on microtidal rocky coasts - Peter Kamstra; Brian Cook; David M. Kennedy; Barbara Brighton (Natural Hazards, 2018)

First identification and characterization of Borrobol‐type tephra in the Greenland ice cores: new deposits and improved age estimates - Eliza Cook; Siwan M. Davies; Esther R. Guðmundsdóttir; Peter M. Abbott; Nicholas J. G. Pearce (Journal of Quaternary Science, 2018)
Contiguous sampling of ice spanning key intervals of the deglaciation from the Greenland ice cores of NGRIP, GRIP and NEEM has revealed three new silicic cryptotephra deposits that are geochemically similar to the well‐known Borrobol Tephra (BT). The BT is complex and confounded by the younger closely timed and compositionally similar Penifiler Tephra (PT). Two of the deposits found in the ice are in Greenland Interstadial 1e (GI‐1e) and an older deposit is found in Greenland Stadial 2.1 (GS‐2.1). Until now, the BT was confined to GI‐1‐equivalent lacustrine sequences in the British Isles, Sweden and Germany, and our discovery in Greenland ice extends its distribution and geochemical composition. However, the two cryptotephras that fall within GI‐1e ice cannot be separated on the basis of geochemistry and are dated to 14358 ± 177 a b2k and 14252 ± 173 a b2k, just 106 ± 3 years apart. The older deposit is consistent with BT age estimates derived from Scottish sites, while the younger deposit overlaps with both BT and PT age estimates. We suggest that either the BT in Northern European terrestrial sequences represents an amalgamation of tephra from both of the GI‐1e events identified in the ice‐cores or that it relates to just one of the ice‐core events. A firm correlation cannot be established at present due to their strong geochemical similarities. The older tephra horizon, found within all three ice‐cores and dated to 17326 ± 319 a b2k, can be correlated to a known layer within marine sediment cores from the North Iceland Shelf (ca. 17179‐16754 cal a BP). Despite showing similarities to the BT, this deposit can be distinguished on the basis of lower CaO and TiO 2 and is a valuable new tie‐point that could eventually be used in high‐resolution marine records to compare the climate signals from the ocean and atmosphere.

Factors affecting distribution and abundance of jellyfish medusae in a temperate estuary: a multi-decadal study - Jason Baumsteiger; Teejay A. O’Rear; Jonathan D. Cook; Amber D. Manfree; Peter B. Moyle (Biological Invasions, 2018)

Defining ecologically relevant scales for spatial protection with long‐term data on an endangered seabird and local prey availability - Richard B. Sherley; Philna Botha; Les G. Underhill; Peter G. Ryan; Danie van Zyl; Andrew C. Cockcroft; Robert J.M. Crawford; Bruce M. Dyer; Timothée R. Cook (Conservation Biology, 2017)
Human activities are important drivers of marine ecosystem functioning. However, separating the synergistic effects of fishing and environmental variability on the prey base of nontarget predators is difficult, often because prey availability estimates on appropriate scales are lacking. Understanding how prey abundance at different spatial scales links to population change can help integrate the needs of nontarget predators into fisheries management by defining ecologically relevant areas for spatial protection. We investigated the local population response (number of breeders) of the Bank Cormorant ( Phalacrocorax neglectus ), a range‐restricted endangered seabird, to the availability of its prey, the heavily fished west coast rock lobster ( Jasus lalandii ). Using Bayesian state‐space modeled cormorant counts at 3 colonies, 22 years of fisheries‐independent data on local lobster abundance, and generalized additive modeling, we determined the spatial scale pertinent to these relationships in areas with different lobster availability. Cormorant numbers responded positively to lobster availability in the regions with intermediate and high abundance but not where regime shifts and fishing pressure had depleted lobster stocks. The relationships were strongest when lobsters 20–30 km offshore of the colony were considered, a distance greater than the Bank Cormorant's foraging range when breeding, and may have been influenced by prey availability for nonbreeding birds, prey switching, or prey ecology. Our results highlight the importance of considering the scale of ecological relationships in marine spatial planning and suggest that designing spatial protection around focal species can benefit marine predators across their full life cycle. We propose the precautionary implementation of small‐scale marine protected areas, followed by robust assessment and adaptive‐management, to confirm population‐level benefits for the cormorants, their prey, and the wider ecosystem, without negative impacts on local fisheries.

Using basic metrics to analyze high-resolution temperature data in the subsurface - Margaret Shanafield; James L. McCallum; Peter G. Cook; Saskia Noorduijn (Hydrogeology Journal, 2017)

Groundwater age, mixing and flow rates in the vicinity of large open pit mines, Pilbara region, northwestern Australia - Peter Cook; Shawan Dogramaci; James McCallum; Joanne Hedley (Hydrogeology Journal, 2017)

Dendritic cells in lung immunopathology - Peter C. Cook; Andrew S. MacDonald (Seminars in Immunopathology, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Development and characterization of a synthetic infectious cDNA clone of the virulent Bucyrus strain of equine arteritis virus expressing mCherry (red fluorescent protein) - Shankar P. Mondal; R. Frank Cook; R. Lakshman Chelvarajan; Pamela J. Henney; Peter J. Timoney; Udeni B. R. Balasuriya (Archives of Virology, 2016)

Meta-studies in land use science: Current coverage and prospects - Jasper van Vliet; Nicholas R. Magliocca; Bianka Büchner; Elizabeth Cook; José M. Rey Benayas; Erle C. Ellis; Andreas Heinimann; Eric Keys; Tien Ming Lee; Jianguo Liu; Ole Mertz; Patrick Meyfroidt; et al. (Ambio, 2016)

Pore‐water exchange driven by tidal pumping causes alkalinity export in two intertidal inlets - Peter A. Faber; Victor Evrard; Ryan J. Woodland; Ian C. Cartwright; Perran L. M. Cook (Limnology and Oceanography, 2014)
Carbon (C) and alkalinity export from two adjacent intertidal inlets with different terrestrial inputs was investigated. One inlet receives a small creek from an agriculturally dominated catchment, leading to the input of terrestrially sourced material, whereas the other is relatively isolated from terrestrial inputs. Using time‐series measurements, we calculated the total advective exchange of dissolved organic C (DOC; 0–25 mmol m ‒2 d ‒1 ), dissolved inorganic C (DIC; 130–450 mmol m ‒2 d ‒1 ), total alkalinity (TA; 46–310 mmol m ‒ d ‒1 ), and the nutrients nitrate (1.0–1.1 mmol m ‒2 d ‒1 ), ammonia (0.0043–0.10 mmol m ‒2 d ‒1 ), and phosphorus (0.016–0.25 mmol m ‒2 d ‒1 ). Radon‐222 ( 222 Rn) data indicated that pore‐water exchange played an important part in controlling C export from the sediment as an advective flux. The residence time of pore water within both inlets was ~ 6.6–7.4 h, indicating that pore‐water exchange is driven by tidal pumping. The inlet with the greater amount of terrestrial inputs exported much more TA (310 vs. 46 mmol m ‒2 d ‒1 ), suggesting that the extent of land‐to‐sea connectivity influences how C is exported. We hypothesize that this is due to the increased input of iron (Fe) from terrestrial sources, which fosters net TA production through the burial of reduced sulfur species as Fe sulfides. A simple mass balance showed that the TA fluxes observed over 24 h were higher than could be sustained continuously with Fe input from the catchment (0.49 mmol Fe m ‒2 d ‒1 ), meaning that the observed TA fluxes could not be sustained on long timescales. It is most likely that there are periods of net reduction and net oxidation in response to wave action and calm conditions, highlighting the importance of long‐term monitoring over different seasons and weather patterns to obtain representative budgets.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

A Framework for Quantitative Assessment of Impacts Related to Energy and Mineral Resource Development - Seth S. Haines; Jay E. Diffendorfer; Laurie Balistrieri; Byron Berger; Troy Cook; Don DeAngelis; Holly Doremus; Donald L. Gautier; Tanya Gallegos; Margot Gerritsen; Elisabeth Graffy; Sarah Hawkins; et al. (Natural Resources Research, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Upper thermal tolerances of key taxonomic groups of stream invertebrates - Barbara A. Stewart; Paul G. Close; Peter A. Cook; Peter M. Davies (Hydrobiologia, 2013)

Dynamics of groundwater‐derived nitrate and nitrous oxide in a tidal estuary from radon mass balance modeling - Wei Wen Wong; Michael R. Grace; Ian Cartwright; M. Bayani Cardenas; Peter B. Zamora; Perran L. M. Cook (Limnology and Oceanography, 2013)
We monitored submarine groundwater discharge (SGD) into the Werribee Estuary, Australia, using both chemical and physical methods. SGD occurred at hotspots where 222 Rn persisted through a 12 month survey period. A significant correlation between 222 Rn and ( r 2 = 0.8, p 222 Rn and N 2 O ( r 2 = 0.6, p 222 Rn hotspot, and much higher and N 2 O concentrations in groundwater relative to surface water suggest that elevated and N 2 O concentrations in the estuary were derived from SGD. Two sampling campaigns over 24 h revealed that variations of 222 Rn,, and N 2 O were controlled by tide‐induced hydraulic‐head gradient fluctuations and, possibly to a much lesser extent, by tidal pumping and density‐driven convection. A two‐box 222 Rn mass‐balance model was used to calculate the rate of SGD into two different layers across the pycnocline of the estuary. A higher total groundwater discharge rate of 0.12 ± 0.09 m d −1 was observed in the surface layer during ebb tide compared with 0.10 ± 0.08 m d −1 during flood tide. Fluxes of groundwater‐derived and N 2 O were higher than the riverine flux at baseflow by more than 30 fold and 20 fold, respectively. SGD derived fluxes exceeded the mean annual riverine and TN fluxes by a factor of ∼ 5 and ∼ 3 respectively. SGD‐derived N 2 O fluxes were 170 µmol m −2 d −1 , which are among the highest N 2 O fluxes observed in estuaries.

A comparison of culture-dependent and culture-independent techniques used to characterize bacterial communities on healthy and white plague-diseased corals of the Montastraea annularis species complex - G. M. Cook; J. P. Rothenberger; M. Sikaroodi; P. M. Gillevet; E. C. Peters; R. B. Jonas (Coral Reefs, 2013)

Holocene environmental change at Lake Shudu, Yunnan Province, southwestern China - Richard T. Jones; Charlotte G. Cook; Enlou Zhang; Peter G. Langdon; Jason Jordan; Chris Turney (Hydrobiologia, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

GPS and time-depth loggers reveal underwater foraging plasticity in a flying diver, the Cape Cormorant - Timothée R. Cook; Maike Hamann; Lorien Pichegru; Francesco Bonadonna; David Grémillet; Peter G. Ryan (Marine Biology, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Non-specific (entropic) forces as major determinants of the structure of mammalian chromosomes - Kieran Finan; Peter R. Cook; Davide Marenduzzo (Chromosome Research, 2011)

Dating of ‘young’ groundwaters using environmental tracers: advantages, applications, and research needs - Brent D. Newman; Karsten Osenbrück; Werner Aeschbach-Hertig; D. Kip Solomon; Peter Cook; Kazimierz Różański; Rolf Kipfer (Isotopes in Environmental and Health Studies, 2010)

Integration of novel SSR and gene-based SNP marker loci in the chickpea genetic map and establishment of new anchor points with Medicago truncatula genome - Spurthi N. Nayak; Hongyan Zhu; Nicy Varghese; Subhojit Datta; Hong-Kyu Choi; Ralf Horres; Ruth Jüngling; Jagbir Singh; P. B. Kavi Kishor; S. Sivaramakrishnan; Dave A. Hoisington; Günter Kahl; et al. (Theoretical and Applied Genetics, 2010)

Marine Metapopulations - Celeste Benham; Alison M. Cawood; Geoffrey S. Cook; Ange Darnell; Peter C. Davison; Miriam C. Goldstein; Ayana Elizabeth Johnson; Talina Konotchick; Elisa M. Maldonado; Alexis L. Pasulka; Jennifer C. Prairie; Serena M. Moseman; et al. (Marine Ecology, 2008)

Deliberate omission or unfortunate oversight: Should stygofaunal surveys be included in routine groundwater monitoring programs? - Moya Tomlinson; Andrew J. Boulton; Peter J. Hancock; Peter G. Cook (Hydrogeology Journal, 2007)

Responses of Phradis parasitoids to volatiles of lavender, Lavendula angustifolia—a possible repellent for their host, Meligethes aeneus - Samantha M. Cook; Martin Jönsson; Matthew P. Skellern; Darren A. Murray; Peter Anderson; Wilf Powell (BioControl, 2007)

The economic viability and potential of a novel poultry agroforestry system - Christopher Yates; Peter Dorward; Gabriel Hemery; Paul Cook (Agroforestry Systems, 2007)

Use of Simulated Annealing for Identifying Essential Fish Habitat in a Multispecies Context - ROSAMONDE R. COOK; PETER J. AUSTER (Conservation Biology, 2005)
Essential fish habitat (EFH) is defined under U.S. federal law, which mandates its protection. Current single‐species approaches to identifying EFH for suites of managed species have resulted in areas designated for protection that are so large that protecting fish habitat has been difficult in the context of fishery management. We evaluated the potential for simulated annealing, a type of mathematical optimization, as a tool for simultaneously identifying EFH for multiple species in four ecological regions of the eastern continental shelf of the United States. Data were obtained from a shelf‐wide trawl survey with site‐specific abundance information spanning 37 years. The data were averaged within units of a sampling grid with 10‐minute squares. We used computer software with an objective function that includes a term for weighting the boundary length of selected sampling units and thereby identifies solutions that meet specific targets for representation under varying degrees of spatial aggregation. We defined representation as a percentage of the cumulative sampled abundance of individual species and examined the effects of these target values and spatial constraints on total (sea‐surface) area and boundary length of solution sets. We also evaluated the algorithm for its ability to select areas where juveniles occurred at high densities as a proxy for habitat value. Annealing solutions covered less total area than would the combined habitats of individual species that capture the same proportion of population abundance. For most species in most solutions, high‐density areas were selected in higher proportions to their relative abundance in a region and solutions contained less total habitat area and smaller boundary lengths. Additionally, sampling units were distributed among two or more discrete localities versus a single location for the same target level of representation. We suggest that simulated annealing is a viable tool for EFH planning with the potential for identifying more spatially conservative habitat areas for protection than a single‐species approach.

Different populations of RNA polymerase II in living mammalian cells - Miki Hieda; Henry Winstanley; Philip Maini; Francisco J. Iborra; Peter R. Cook (Chromosome Research, 2005)

A high affinity ligand for GABA A -receptor containing a 5 subunit antagonizes ethanol?s neurobehavioral effects in Long-Evans rats - Peter F. McKay; Katrina L. Foster; Dynesha Mason; Shannan McCane; Xiaohui He; Harry L. June; James M. Cook; Rancia Cummings; Marin Garcia; La Shone Williams; Collette Grey (Psychopharmacology, 2004)

The Use of Clinical Trial Simulation to Support Dose Selection: Application to Development of a New Treatment for Chronic Neuropathic Pain - Peter A. Lockwood; Jack A. Cook; Wayne E. Ewy; Jaap W. Mandema (Pharmaceutical Research, 2003)

Analysis of soil wetting and solute transport in subsurface trickle irrigation - Claire M. Cote; Keith L. Bristow; Philip B. Charlesworth; Freeman J. Cook; Peter J. Thorburn (Irrigation Science, 2003)

WetUp: a software tool to display approximate wetting patterns from drippers - Freeman J. Cook; Peter J. Thorburn; Peter Fitch; Keith L. Bristow (Irrigation Science, 2003)

Soil-dependent wetting from trickle emitters: implications for system design and management - Peter J. Thorburn; Freeman J. Cook; Keith L. Bristow (Irrigation Science, 2003)

PATHOGENICITY OF CHORISTONEURA FUMIFERANA NUCLEOPOLYHEDROVIRUS PROPAGATED IN VITRO AT DIFFERENT INCUBATION TEMPERATURES - PETER M. EBLING; GUIDO F. CAPUTO; BARBARA J. COOK (In Vitro Cellular & Developmental Biology - Animal, 2003)

Pathogencity of a nucleopolyhedrovirus (CfMNPV)propagated in vitro at different incubation temperatures - Peter Ebling; Guido Caputo; Barbara Cook (In Vitro Cellular & Developmental Biology - Animal, 2003)

Using groundwater levels to estimate recharge - Richard W. Healy; Peter G. Cook (Hydrogeology Journal, 2002)

Choosing appropriate techniques for quantifying groundwater recharge - Bridget R. Scanlon; Richard W. Healy; Peter G. Cook (Hydrogeology Journal, 2002)

Theme issue on groundwater recharge - Bridget R. Scanlon; Peter G. Cook (Hydrogeology Journal, 2002)

Congruent patterns of genetic variation in a burrowing freshwater crab revealed by allozymes and mt DNA sequence analysis - Savel R. Daniels; Barbara A. Stewart; Peter A. Cook (Hydrobiologia, 2002)

Acute leukemia in electrical workers: a New Zealand case–control study - Peter Bethwaite; Angus Cook; Josephine Kennedy; Neil Pearce (Cancer Causes & Control, 2001)

Estimating uncertainty in fish stock assessment and forecasting - Kenneth Patterson; Robin Cook; Chris Darby; Stratis Gavaris; Laurence Kell; Peter Lewy; Benoît Mesnil; André Punt; Victor Restrepo; Dankert W. Skagen; Gunnar Stefánsson (Fish and Fisheries, 2001)
A variety of tools are available to quantify uncertainty in age‐structured fish stock assessments and in management forecasts. These tools are based on particular choices for the underlying population dynamics model, the aspects of the assessment considered uncertain, and the approach for assessing uncertainty (Bayes, frequentist or likelihood). The current state of the art is advancing rapidly as a consequence of the availability of increased computational power, but there remains little consistency in the choices made for assessments and forecasts. This can be explained by several factors including the specifics of the species under consideration, the purpose for which the analysis is conducted and the institutional framework within which the methods are developed and used, including the availability and customary usage of software tools. Little testing of either the methods or their assumptions has yet been done. Thus, it is not possible to argue either that the methods perform well or perform poorly or that any particular conditioning choices are more appropriate in general terms than others. Despite much recent progress, fisheries science has yet to identify a means for identifying appropriate conditioning choices such that the probability distributions which are calculated for management purposes do adequately represent the probabilities of eventual real outcomes. Therefore, we conclude that increased focus should be placed on testing and carefully examining the choices made when conducting these analyses, and that more attention must be given to examining the sensitivity to alternative assumptions and model structures. Provision of advice concerning uncertainty in stock assessments should include consideration of such sensitivities, and should use model‐averaging methods, decision tables or management procedure simulations in cases where advice is strongly sensitive to model assumptions.

Evidence of deep circulation in two perennially ice‐covered Antarctic lakes - Scott W. Tyler; Peter G. Cook; Anya Z. Butt; James M. Thomas; Peter T. Doran; W. Berry Lyons (Limnology and Oceanography, 1998)
The perennial ice covers found on many of the lakes in the McMurdo Dry Valley region of the Antarctic have been postulated to severely limit mixing and convective turnover of these unique lakes. In this work, we utilize chlorofluorocarbon (CFC) concentration profiles from Lakes Hoare and Fryxell in the McMurdo Dry Valley to determine the extent of deep vertical mixing occurring over the last 50 years. Near the ice‐water interface, CFC concentrations in both lakes were well above saturation, in accordance with atmospheric gas supersaturations resulting from freezing under the perennial ice covers. Evidence of mixing throughout the water column at Lake Hoare was confirmed by the presence of CFCs throughout the water column and suggests vertical mixing times of 20–30 years. In Lake Fryxell, CFC‐11, CFC‐12, and CFC‐113 were found in the upper water column; however, degradation of CFC‐ 11 and CFC‐ 12 in the anoxic bottom waters appears to be occurring with CFC‐ 113 only present in these bottom waters. The presence of CFC‐113 in the bottom waters, in conjunction with previous work detecting tritium in these waters, strongly argues for the presence of convective mixing in Lake Fryxell. The evidence for deep mixing in these lakes may be an important, yet overlooked, phenomenon in the limnology of perennially icecovered lakes.

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

An assessment of the use of low-level aerobic swimming in promoting recovery from handling stress in rainbow trout - Walter F. Meyer; Peter A. Cook (Aquaculture International, 1996)

A recombinant fowlpox virus that expresses the VP2 antigen of infectious bursal disease virus induces protection against mortality caused by the virus - C. D. Bayliss; R. W. Peters; Jane K. A. Cook; R. L. Reece; K. Howes; M. M. Binns; M. E. G. Boursnell (Archives of Virology, 1991)

Taxonomic studies on strains of avian infectious bronchitis virus using neutralisation tests in tracheal organ cultures - J. H. Darbyshire; J. G. Rowell; Jane K. A. Cook; R. W. Peters (Archives of Virology, 1979)

Growth comparisons of avian infectious bronchitis virus strains in organ cultures of chicken tissues - J. H. Darbyshire; Jane K. A. Cook; R. W. Peters (Archives of Virology, 1978)

The use of chicken tracheal organ cultures for the isolation and assay of avian infectious bronchitis virus - Jane K. A. Cook; J. H. Darbyshire; R. W. Peters (Archives of Virology, 1976)

Characterization of hypoxanthine-guanine phosphoribosyl transferase in man-mouse somatic cell hybrids by an improved electrophoretic method - Seung-il Shin; P. Meera Khan; Peter R. Cook (Biochemical Genetics, 1971)